Solvent effect on translational diffusivity and orientational mobility of polymers in solution: A molecular dynamics study - Bahar, Ivet; Badur, Bertan; Doruker, Pemra (The Journal of chemical physics, 1993)
Molecular dynamics simulations have been performed for a bead–spring model chain of 30 beads immersed in 738 solvent molecules. The solvent–solute interaction energy εbs has been varied in the range 0.1≤εbs≤0.8 kcal/mol to assess the role and importance of solvent type on the dynamic and equilibrium properties of the chain. Radial distribution functions for polymer bead–solvent and bead–bead pairs indicate the enhancement of more expanded chain configurations with increasing quality of the solvent. The translational diffusivity D of the chain exhibits an inverse linear dependence on εbs, thus decreasing in the presence of more favorable polymer–solvent interactions. Molecular dimensions of the chain such as the mean-square end-to-end distance 〈r2〉 and the radius of gyration Rg are examined in various solvent environment. The ratio 〈r2〉/Rg2 approximates the limiting value of 6 corresponding to infinitely long freely jointed chains. A linear dependence of D on 1/Rg is observed, in conformity with the Zimm theory of dilute polymer solutions subject to hydrodynamic interactions. The orientational motion of internal chain vectors is also found to slow down with increasing strength of intermolecular interactions, in parallel with the translational diffusivity. Characteristic orientational relaxation times τ are calculated for chain segments of various sizes n, using the initial decay rates of the corresponding orientational autocorrelations functions. These are found to obey a scaling law of the form τ∼na for a given εbs. The exponent a therein decreases with the quality of the solvent, assuming values in the interval 1.0≤a≤1.5 throughout the investigated range of polymer–solvent interactions.